Identifying the Peculiarities of Students’ Aggressive Behaviour in Physical Education Lessons - Sniras, Sarunas (Physical Education Theory and Methodology, 2024)
Background. Recently, a lot of special attention has been paid to the school environment where students’ aggressive behaviour that spreads quickly is getting more expressed and reflects processes in the modern society and their consequences for the young generation. It can often have various short- and long-term consequences for a student’s behaviour, communication with others, emotional state or his/her self-esteem. Thus, this complex situation encourages to get interested in understanding the underlying causes of students’ aggressive behaviour and peculiarities of its frequent manifestation. Objectives. The study aimed to reveal the peculiarities of students’ aggressive behaviour expression in physical education lessons in the context of age and gender aspects. Material and methods. A total of 197 students participated in the study, comprising 52 girls aged 12-13 years, 44 boys of the same age group, 60 girls aged 14-15 years and 41 boys of the same age. Results. The findings of the study indicated that 14-15-year-old students were more prone to the following forms of aggressive behaviour in physical education lessons: negativism, offence, irritation, physical and verbal aggression compared with 12-13-year-old students. It was also determined that older students demonstrated statistically significant higher levels of hostility and aggressiveness than younger counterparts. When analysing the students’ aggressive behaviour in the aspect of gender, it was found that boys often expressed the following forms of aggressive behaviour: negativism, offence, irritation and physical aggression; meanwhile, girls were more prone to the feeling guilty and verbal aggression. Higher hostility is more characteristic to boys than to girls, but the aggressiveness observed in the groups of boys and girls was assessed similarly according to the aggressiveness index. Conclusions. The results obtained could be subjected to further analysis in order to enhance their effectiveness, for example, by examining concrete life situations of students.